T-type calcium channels in the orbitofrontal cortex mediate sensory integration as measured using a spontaneous oddity task in rats - Marks, Wendie N. (Learn Mem, 2018)
The roles of low-voltage-activated (T-type) calcium channels in brain diseases have been studied extensively. Less is known regarding the involvement of T-type channels in cognition and behavior. Sensory integration (SI) is a cognitive process whereby the brain uses unimodal or multimodal sensory features to create a comprehensive representation of the environment. The multisensory object oddity (MSO) task assesses SI using combinations of sensory features of objects, either in the same or different sensory modalities. The regulation of SI involves the orbitofrontal cortex (OFC), an area which shows high levels of T-type calcium channel expression. We tested the effects of blocking T-type calcium channels on the MSO task with the selective T-type antagonist, Z944 (5 mg/kg; i.p. systemic; 100 or 500 µM OFC infusion), in male Long Evans rats. With systemic treatment, Z944 impaired the visual and visual-olfactory versions of the task. Infusion of 100 and 500 µM Z944 produced deficits in the olfactory version of the task. In addition, only vehicle-infused, but not Z944-infused, rats showed significant performance above chance for all task variants. Thus, the present results suggest that T-type calcium channels in OFC are involved in SI of features in an oddity task. Given that unimodal SI was disrupted by OFC infusions of Z944, the deficits in the multimodal task must be interpreted with caution. As SI is disrupted in psychiatric disorders, further investigations elucidating the brain regions implicated in SI regulation by T-type calcium channels may help inform therapeutic development for those suffering from SI impairments.